ANALISIS STRATEGI PEMASARAN BOX KEMASAN ARIFINPACKAGING DENGAN METODE SWOT DAN QSPM - Hasna Rafifah Azmi (2022)
Arifin Packaging is one of the businesses engaged in the manufacture of packaging box made of cardboard. Arifin Packaging produces packaging box with various sizes from the smallest to the largest according to customer wishes. The problem with this business is that Arifin Packaging still depends on the number of orders from customers made in the pre-order system for 3-5 days and in marketing its products only by word of mouth, so that the scope of its sales has not been reached by the wider community. The purpose of this research is to determine the best business strategy for the company by considering internal and external factors. This study uses the IFE and EFE matrix methods, IE matrix, SWOT matrix, and QSPM. The IE metric results show that Arifin Packaging is in cell II, which is growing and building. Based on the IE matrix and the SWOT matrix, there are five methods produced. Furthermore, in the last stage, namely the calculation of QSPM by comparing the proposed strategy and the existing strategy, it is obtained that the total value of the greatest attraction as a prioritized strategy is the proposed strategy.